2004
DOI: 10.1080/19404476.2004.11658176
|View full text |Cite
|
Sign up to set email alerts
|

Young Adolescent Voices: Students’ Perceptions of Interdisciplinary Teaming

Abstract: Interdisciplinary teaming in middle schools has increased dramatically over the past few decades (McEwin, Dickinsen & Jensen, 2003); nevertheless, students have rarely been consulted as important sources of insight into this practice (Dickinsen & Erb, 1997) of two or more teachers sharing the responsibility for instruction, curriculum, and assessment of a common group of students (NMSA, 1995). The purpose of this study was to describe and analyze young adolescents' perceptions of effective interdisciplinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Our findings are consistent with the body of research that indicates positive effects from employing integrated curricula (Bailey, 2003;Boyer & Bishop, 2004;Lewis & Shaha, 2003;Lieberman & Hoody, 1998;Morrone, 2001;Vars, 2001;Warren & Payne, 1997). Partly because of this emerging research, a surge in the use of integrated curricula and interdisciplinary teaching practices occurred from the late 1970s through the late 1980s (Drake & Burns, 2004;Palmer, 1998).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are consistent with the body of research that indicates positive effects from employing integrated curricula (Bailey, 2003;Boyer & Bishop, 2004;Lewis & Shaha, 2003;Lieberman & Hoody, 1998;Morrone, 2001;Vars, 2001;Warren & Payne, 1997). Partly because of this emerging research, a surge in the use of integrated curricula and interdisciplinary teaching practices occurred from the late 1970s through the late 1980s (Drake & Burns, 2004;Palmer, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…The results of another study (Lewis & Shaha, 2003) indicated that an integrated curriculum was superior to other curricula in improving student achievement and attitudes about learning. Boyer and Bishop (2004) reported that interdisciplinary, multiyear teaming resulted in enhancing students' personal growth, including confidence, independence, tolerance, leadership, collaborative skills, and sense of belonging. Focusing on the effects on teachers, Warren and Payne (1997) found that an integrated teaming experience increased teacher efficacy and beliefs about the teaching environment.…”
mentioning
confidence: 99%
“…Reform-based practices include inquiry-based, hands-on, cooperative, and problembased teaching for depth of student understanding. Interdisciplinary team projects can also enhance students' personal growth, including confidence, independence, tolerance, leadership, collaborative skills, and sense of belonging [3].…”
Section: Expandingmentioning
confidence: 99%
“…These benefits are well-documented in the literature. For example, past research demonstrates that students in interdisciplinary teams have higher scores on standardized achievement tests, are more academically engaged, and have greater feelings of school belonging (Boyer & Bishop, 2004; Flowers & Mertens, 2003; Flowers, Mertens, & Mulhall, 1999; Lee & Smith, 1993; Wallace, 2007). …”
Section: Interdisciplinary Teaming In Middle Schoolmentioning
confidence: 99%